Pollution atmosphérique en milieu urbain : de sa régulation à sa surveillance - Laurence Lestel (VertigO, 2012)
In the early nineteenth century, denounced pollution is visible and from industrial origin. Despite the effort to measure the quality of indoor air, there was neither measurement nor a definition of air quality for outdoor air. The given answers were technical (decrease of smoke emission) and regulations. Pollution from other sectors (urban uses, transport) due to the increased use of coal was not taken into account. In France, the first systematic analyses of atmospheric air are those of the Montsouris Observatory since 1876. Gradually, the regulation incorporates discharge limits, primarily for industrial black smoke (1934 in the department of the Seine) and for discharges of motor vehicles (Decrees of 1969). Episodes of increased mortality resulting from the combination of weather events and gas emissions lead to the establishment of monitoring networks in 1954 in Paris through the efforts of the Laboratory of Hygiene of the city of Paris, and the central Laboratory of the Préfecture de Police, and in all major cities and industrial areas of France since 1973. The organization of these monitoring networks was strengthened by the Air Act of 1996.